University College : a portrait, 1853-1953 - Bissell, Claude Thomas, 1916-2000 (University of Toronto Press, 1953)
For a century University College has had a profound and continuous influence on the cultural development of Canada. The authors of this volume show us University College as a political and educational institution; as a physical structure that has aroused admiration and scholarly curiosity; as the home of a long line of great teachers and scholars, and of a student body diverse in its origins and spirited in its attitudes; and finally, as the embodiment of an educational idea that transcends curricula and prescriptions.